2006
DOI: 10.1002/ajim.20403
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Center for Epidemiologic Studies Depression Scale as a screening instrument of major depressive disorder among Japanese workers

Abstract: The validity of CES-D is confirmed and it is a valid instrument for detecting MDD in working populations in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 20 publications
2
92
0
Order By: Relevance
“…Studies of other populations have found the optimal cut point to be higher than the traditional value of 16, with most being between 18 and 22. 13,[27][28][29][30][31] In the present work, we analyzed the data using both the traditional cutoff of 16, as well as the more stringent cutoff of 22 recommended by Haringsma et al, 13 and found an association of hypogonadism with the more overt depression scores. This finding agrees in part only with that of Delhez et al, 32 who also found that hypogonadism was associated with depressive scores, but reported that this association was strongest in men with mild depression symptoms, as opposed to pathological cases.…”
Section: Discussionmentioning
confidence: 95%
“…Studies of other populations have found the optimal cut point to be higher than the traditional value of 16, with most being between 18 and 22. 13,[27][28][29][30][31] In the present work, we analyzed the data using both the traditional cutoff of 16, as well as the more stringent cutoff of 22 recommended by Haringsma et al, 13 and found an association of hypogonadism with the more overt depression scores. This finding agrees in part only with that of Delhez et al, 32 who also found that hypogonadism was associated with depressive scores, but reported that this association was strongest in men with mild depression symptoms, as opposed to pathological cases.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, the levels of serum ferritin concentrations were lower in men with a higher prevalence of depressive symptoms; the association, however, was statistically significant only when the presence of depressive symptoms was defined by using the cutoff of ≥19 on the CES-D scale. Although the cutoff for CES-D of ≥16 has been widely recommended, the cutoff of ≥19 has been recommended and validated for use among Japanese workers with the sensitivity and specificity of 92.7% and 91.8%, respectively (Wada et al, 2007). Such a higher cutoff is reasonable given that Japanese tend to express their positive emotion in a modest manner, leading to a high score on depression scales (Iwata et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…We defined depressive symptoms as present when a subject had a CES-D score of ≥16. Other cutoff values for the definition were also used: ≥ 19 that has been recommended for use among Japanese workers and ≥ 23 indicative of severe depressive state (Wada et al, 2007).…”
Section: Depressive Symptomsmentioning
confidence: 99%
“…Depressive symptoms were defined as present when subjects had a CES-D score of X16. Other cutoff values for the definition were also used: X19 that may be suitable for Japanese (Wada et al, 2007) and X23 indicative of severe depressive state (Wada et al, 2007).…”
Section: Depressive Symptomsmentioning
confidence: 99%